2004
DOI: 10.1007/s00432-003-0523-x
|View full text |Cite
|
Sign up to set email alerts
|

Chemoembolization of rat liver metastasis with irinotecan and quantification of tumor cell reduction

Abstract: In conclusion, the effect of HACE with irinotecan surpassed that of HACE with 5-FU and prompts further investigation in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…This application method increases the regional uptake of a coadministered drug and reduces the systemic drug concentration (Ball 1991, Starkhammar andHakansson 1987). Recently it was demonstrated preclinically that HACE enables the locoregional use of drugs without significant first-path effect in the liver (Saenger et al 2004). To date, few clinical studies have shown a benefit in survival following HACE for certain lesions, such as hepatocellular carcinoma (Llovet et al 2002) or liver metastases of colorectal cancer (Lang and Brown, Jr. 1993, Sanz-Altamira et al 1997, Tellez et al 1998).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This application method increases the regional uptake of a coadministered drug and reduces the systemic drug concentration (Ball 1991, Starkhammar andHakansson 1987). Recently it was demonstrated preclinically that HACE enables the locoregional use of drugs without significant first-path effect in the liver (Saenger et al 2004). To date, few clinical studies have shown a benefit in survival following HACE for certain lesions, such as hepatocellular carcinoma (Llovet et al 2002) or liver metastases of colorectal cancer (Lang and Brown, Jr. 1993, Sanz-Altamira et al 1997, Tellez et al 1998).…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that drugs, even without significant first-path effect, such as irinotecan (Saenger et al 2004) or gemcitabine , can be used to reduce the tumor load in the liver more successfully than 5-FU when coadministered with starch microspheres into the hepatic artery (HACE).…”
mentioning
confidence: 99%
“…Tumor cell preparation and transplantation were conducted as previously described [12,18,19]. Briefly, for in vivo injection, 4 9 10 6 tumor cells were suspended in 0.2 ml phosphate buffered saline (PBS) without calcium and magnesium ions.…”
Section: In Vivo Inoculationmentioning
confidence: 99%
“…The rat model was chosen as a suitable model for TACE using the DEB, as it was previously demonstrated using this model that there was significant activity of irinotecan in terms of complete remission in 44% of rats and reduction of the mean tumor cell load by 66% [12]. In this model CC53l-lacZ cells are transplanted by portal vein injection into male WAG/Rij rats and detection of tumor cells is accomplished by measuring their b-galactosidase activity.…”
mentioning
confidence: 99%
“…Thus, the comparison of HACE with 5-FU or Gem showed that the efficacy of Gem in reducing the hepatic tumor cell load was significantly higher and its therapeutic ratio was greater than that of 5-FU. In a subsequent experiment, the effect of HACE with irinotecan was compared vs. 5-FU as a standard agent in rat liver metastasis (Saenger, et al, 2004). Briefly, 4 × 10 6 CC531-lac-Z cells were intraportally injected into male Wag/Rij rats.…”
Section: Generation Of the Modelmentioning
confidence: 99%